A Canine Leptospirosis Clinical Case Due to Leptospira interrogans (Serogroup Icterohaemorrhagiae) in a Dog Kennel in Castelvetrano (Western Sicily, South Italy) - Francesca Grippi; Valeria Blanda; Paola Galluzzo; Manuel Bongiorno; Carmela Sciacca; Francesca Arcuri; Rosalia D’Agostino; Ilenia Giacchino; Francesca Gucciardi; Mario D’Incau; Cristina Bertasio; Alessandra Torina; et al. (Veterinary Sciences, 2023)
Leptospirosis is a worldwide widespread zoonosis caused by Leptospira genus. We report an acute leptospirosis case in a puppy housed at a municipal kennel and the subsequent diagnostic investigations carried out on all dogs housed in the kennel. Laboratory investigation included mainly a microagglutination test, real-time PCR, and multi-locus sequence typing (MLST) for Leptospira genus. Other agents of infection were excluded. The puppy resulted positive for Leptospira interrogans Icterohaemorrhagiae both with serological and molecular assays. All of the other 66 dogs in the kennel underwent clinical and laboratory investigations twice, 15 days apart. No other dog showed leptospirosis clinical signs. At the first sampling, eight dogs (12%) showed antibodies against Leptospira interrogans serogroup Icterohaemorragiae serovar Copenhageni. Real-time PCR on urine samples of seropositive dogs detected Leptospira spp. DNA in one sample, then identified as Leptospira interrogans serogroup Icterohaemorragiae by MLST. Fifteen days after, four of the previous seropositive dogs still showed antibodies against Leptospira spp. All urine samples collected from seropositive dogs were negative at real-time PCR. The study allowed the early confirmation of a Leptospirosis case and the identification of at least one asymptomatic carrier of pathogenic Leptospira spp. The prompt activation of all appropriate management measures allowed limiting and extinguishing the infection.